UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN METODE INDEKS CARD MATCH SISWA KELAS VIIIA SMP NEGERI 19 MERANGIN - Badariah, S.Pd (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
This research is based on students' mathematics learning outcomes which are still low. Mathematics learning is still a scourge for some students, so the learning process applied by teachers has not been able to improve student learning outcomes. At SMP Negeri 19 Merangin, the average student who completes learning mathematics is only 44% or still less than the KKM set, which is 75. To overcome this, classroom action is carried out by carrying out the learning process using the card match index model for students. class VIIIA SMP Negeri 19 Merangin. Based on the results of classroom action research which was carried out in 3 cycles, the research subjects were class VIIIA students, totaling 25 students. After the implementation of learning using the card match index model, the student learning outcomes obtained from 5 items tested to students, the average percentage of student learning outcomes has increased in each cycle. in the first cycle of 65.48%, the second cycle, 74.08% and the third cycle, 82.76%. While the activeness of students seen from their activities has increased by 60.40% in the first cycle, to 72.40% in the second cycle and at the end of the third cycle to 74.80%. From these results, it can be concluded that the Index Card Match method can improve student learning outcomes for class VIIIA SMP Negeri 19 Merangin for the 2020/2021 academic year.